Sharing Experiences: Establishing an Expertise Centre on the Protection of Dutch Cultural Heritage - Vermeulen, Theo (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
In the Netherlands an Expertise Centre on the Protection of Dutch Cultural Heritage is being established to bring together scattered knowledge and expertise on collection safety and security issues. A website is being set up based on a broad, integrated security concept. The website will include the DICE database for incident registration. More specialised expertise will be made available on demand. The Centre has been funded for two years, whereupon its viability will be assessed. For the Centre to become a success, the entire cultural heritage field should overcome its reluctance to share sensitive information and commit itself to the Centre.